2011
DOI: 10.1371/journal.pone.0028404
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Array-CGH Studies Implicates Antiviral Immunity Pathways in the Development of Hepatocellular Carcinoma

Abstract: BackgroundThe development and progression of hepatocellular carcinoma (HCC) is significantly correlated to the accumulation of genomic alterations. Array-based comparative genomic hybridization (array CGH) has been applied to a wide range of tumors including HCCs for the genome-wide high resolution screening of DNA copy number changes. However, the relevant chromosomal variations that play a central role in the development of HCC still are not fully elucidated.MethodsIn present study, in order to further chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…Using array CGH analysis from four studies, it was revealed that loci with genomic gains with a prevalence of >25% included 1q, 6p, 8q, 17q, 20p, 5p15.33 and 9q34. 2-34.3, and loci with genomic loss with prevalence of >25% comprised 4q, 6q, 8p, 9p, 13q, 14q, 16q and 17p, and were associated with 31 classical molecular pathways, particularly the antivirus immunological pathway (6).…”
Section: Introductionmentioning
confidence: 99%
“…Using array CGH analysis from four studies, it was revealed that loci with genomic gains with a prevalence of >25% included 1q, 6p, 8q, 17q, 20p, 5p15.33 and 9q34. 2-34.3, and loci with genomic loss with prevalence of >25% comprised 4q, 6q, 8p, 9p, 13q, 14q, 16q and 17p, and were associated with 31 classical molecular pathways, particularly the antivirus immunological pathway (6).…”
Section: Introductionmentioning
confidence: 99%
“…Meta‐analysis is a systematic and quantitative analytical method that can be used to summarize and cross‐analyze the significance of results from multiple studies on the same disease . To date, only a few meta‐analysis studies have been conducted using assay CGH data . A critical prerequisite for this analysis was the requirement to standardize data of previously published CNAs through cross‐platform analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In one meta-analysis, using conventional CGH analysis with low resolution (approximately 2 Mb) from several studies, it was revealed that the most prominent changes were gains of 1q (57.1%), 8q (46.6%), 6p (23.3%), and 17q (22.2%); and losses of 8p (38%), 16q (35.9%), 4q (34.3%), 17p (32.1%), and 13q (26.2%). [25] Using array CGH analysis from four studies, it was revealed that loci with genomic gains with a prevalence of more than 25% included 1q, 6p, 8q, 17q, 20p, 5p15.33, and 9q34.2-34.3; and loci with genomic losses with prevalence of more than 25% comprised 4q, 6q, 8p, 9p, 13q, 14q, 16q, and 17p; and were associated with 31 classical molecular pathways, particularly the antivirus immunological pathway. [25] A series of tumor suppressor genes have been identified in these regions, such as PR domain containing 5 (PRDM5, 4q26), TP53 (17p13.1), retinoblastoma 1 (RB1, 13q14), and cadherin 1, type 1 (CDH1, 16q22.1).…”
Section: Single Nucleotide Polymorphismmentioning
confidence: 99%
“…[25] A series of tumor suppressor genes have been identified in these regions, such as PR domain containing 5 (PRDM5, 4q26), TP53 (17p13.1), retinoblastoma 1 (RB1, 13q14), and cadherin 1, type 1 (CDH1, 16q22.1). [26][27][28] Some clinicopathological associations have been noted with specific abnormalities: Losses of 4q, 13q, and 16q are associated with HBV infection, [25] loss of 4q has been associated with elevated α-fetoprotein levels, TP53 mutations, [29] tumor size, and vascular invasion [30] while 9p and 6q losses have been reported to be independent predictors of poor outcome of HCC patients, [31] and that losses of 4q, 13q, and 16q are associated with HBV infection.…”
Section: Single Nucleotide Polymorphismmentioning
confidence: 99%